Nutritional Support for Pediatric Severe Traumatic Brain Injury - Elliott, Elizabeth; Shoykhet, Michael; Bell, Michael J.; Wai, Kitman (Frontiers in Pediatrics, 2022)
In critically ill children with severe traumatic brain injury (sTBI), nutrition may help facilitate optimal recovery. There is ongoing research regarding nutritional practices in the pediatric intensive care unit (PICU). These are focused on identifying a patient’s most appropriate energy goal, the mode and timing of nutrient delivery that results in improved outcomes, as well as balancing these goals against inherent risks associated with nutrition therapy. Within the PICU population, children with sTBI experience complex physiologic derangements in the acute post-injury period that may alter metabolic demand, leading to nutritional needs that may differ from those in other critically ill patients. Currently, there are relatively few studies examining nutrition practices in PICU patients, and even fewer studies that focus on pediatric sTBI patients. Available data suggest that contemporary neurocritical care practices may largely blunt the expected hypermetabolic state after sTBI, and that early enteral nutrition may be associated with lower morbidity and mortality. In concordance with these data, the most recent guidelines for the management of pediatric sTBI released by the Brain Trauma Foundation recommend initiation of enteral nutrition within 72 hours to improve outcome (Level 3 evidence). In this review, we will summarize available literature on nutrition therapy for children with sTBI and identify gaps for future research.